Recursos digitales en el aula invertida en estudiantes de educación general básica, Unidad Educativa 10 de Agosto - Aguirre Escobar, Arthur Andre (2023)
In the present research topic on digital resources in the inverted classroom in students of basic general education, the general objective is "To analyze the importance of digital resources in the inverted classroom in students of basic general education, Educational Unit 10 de Agosto", having as reference the inclusion of digital and technological resources for the educational development of students in order to promote new educational competencies for learning, proposing an inverted classroom model that allows a better interaction between the teacher and the student. The research methodology will be of basic type, in a descriptive and explanatory approach, the non-experimental research design for a population of 100 students corresponding to the ninth year who will be applied a data collection technique such as the survey used as an instrument the questionnaire itself which is composed of 10 questions about digital resources and their use in classes within a Likert value scale between 0 to 4. The results obtained allowed us to know that there is an availability of students for the application of the inverted classroom methodology with the application of platforms such as Kahoot, Liveworksheets, Genially, among others that promote creativity and initiative in students. Concluding that the use of digital resources in the classroom through an inverted classroom methodology generates positive stimuli in the students' desire to learn, and therefore will improve their academic performance inside and outside the classroom.